Peran Pemerintah Desa dalam Mengelola Sanitasi Lingkungan Guna Mewujudkan Kesejahteraan Masyarakat Desa Perkebunan Bukit Lawang - Edgina Rosselin Br Tarigan; Efi Brata Madya (Faculty of Social Science, Universitas Negeri Padang, 2023)
This research aims to find out the role of the village government in managing environmental sanitation in order to realize the welfare of the people of Bukit Lawang plantation village. The method used is descriptive qualitative. Village government informants as many as 5 people. Location of Bukit Lawang Plantation Village. The research was conducted for 10 days, namely from June 22 to July 02, 2023 with data collection techniques with observation, interviews and documentation and the data source is divided into two, namely primary data from informants and then analyzed using analysis techniques with four processes, namely data collection, data reduction, data display and data verification Then tested data validity by using Triangulation of sources, techniques and time. The results of this study explain that the activities spearheaded by the village government towards the village community are very good and have progressed. This is evident from the people of Bukit Lawang Government Village who can enjoy a clean, healthy and safe environment. Good sanitation contributes significantly to people's health, comfort and quality of life. With this this activity can be declared a success and the awareness of the Bukit Lawang Plantation Village community is increasing until now. In conclusion, the government plays an important role in the empowerment and welfare of the Bukit Lawang village community.